Case Report: Fetomaternal hemorrhage and its association with pronounced neonatal anemia - Li, Peng; Shu, Hua; Lin, Peng; Wang, Jishui; Zhang, Di; Man, Dongmei; Wang, Fengge (Frontiers in Pediatrics, 2024)
Fetomaternal hemorrhage (FMH) is a perplexing obstetric condition that predominantly occurs during the third trimester or at the time of delivery. Its insidious and non-specific onset often leads to diagnostic challenges. The underlying pathophysiology of FMH remains incompletely understood, though it is primarily attributed to compromise of the placental barrier. The severity of the condition is intrinsically associated with the volumn of blood loss, the hemorrhage rate, and the presence of alloimmunity. Upon the occurrence of severe FMH, it can rapidly lead to intrauterine distress, fetal anemia, and the possibility of fetal demise, presenting a considerable threat to both maternal and neonatal well-being. In this article, I present a substantial case of FMH and conduct a systematic review of the current scientific literature regarding the etiology, clinical manifestations, diagnostic approaches, treatment highlights, and prognosis of this condition. The objective of this work is to improve clinicians' comprehension and diagnostic proficiency concerning FMH.